Small diameter vascular grafts: progress on electrospinning matrix/stem cell blending approach - Wang, Nuoxin; Chen, Jiajing; Hu, Qingqing; He, Yunfeng; Shen, Pu; Yang, Dingkun; Wang, Haoyuan; Weng, Dong; He, Zhixu (Frontiers in Bioengineering and Biotechnology, 2024)
The exploration of the next-generation small diameter vascular grafts (SDVGs) will never stop until they possess high biocompatibility and patency comparable to autologous native blood vessels. Integrating biocompatible electrospinning (ES) matrices with highly bioactive stem cells (SCs) provides a rational and promising solution. ES is a simple, fast, flexible and universal technology to prepare extracellular matrix-like fibrous scaffolds in large scale, while SCs are valuable, multifunctional and favorable seed cells with special characteristics for the emerging field of cell therapy and regenerative medicine. Both ES matrices and SCs are advanced resources with medical application prospects, and the combination may share their advantages to drive the overcoming of the long-lasting hurdles in SDVG field. In this review, the advances on SDVGs based on ES matrices and SCs (including pluripotent SCs, multipotent SCs, and unipotent SCs) are sorted out, and current challenges and future prospects are discussed.